Effect of Work Planning and Supervision at Workplace on Employee Effectiveness at Operational Bureau of PT BPR Kencana in Cimahi City - Dede Iskandar Dinata; Nurul Hermina (Universitas Proklamasi 45, 2023)
PT BPR Kencana in Cimahi City, West Java, has carried out activities to increase work planning and supervision at work, especially within the Operations Bureau. This study aims to determine how much influence work planning and supervision at the workplace have on the effectiveness of the employees of the Operational Bureau of PT BPR Kencana in Cimahi City. The research method used in this research is the descriptive-verification research method and the population in this research is the employees of the Operational Bureau, totaling 35 employees. The results showed that work planning variables affect the work effectiveness of the Operational Bureau of PT BPR Kencana in Cimahi City by 15.7 percent. Besides that, supervision at the workplace has an effect of 31.8 percent on the work effectiveness of the employees of the Operational Bureau of PT BPR Kencana in Cimahi City. Work planning and supervision at the workplace have less influence simultaneously influencing the work effectiveness of employees at the Operational Bureau of PT BPR Kencana in Cimahi City.